Perkuliahan dengan Teknik Diskusi: Upaya Meningkatkan Hasil Belajar Mahasiswa pada Materi Kewirausahaan - Sudjoko S (Universitas Wiralodra, 2021)
The subject of Enterpreneurship has 2 semester credit system which must be taught to students of college in Indonesia, for all study programes. The objective of this research is how to improve students’ score of learning teaching process of Enterpreneurship by using teamwork of written proposal and writing compile as their individual task. Research method uses classroom action research, actually, the researcher as a teacher and researcher in this class. The result of research shows that, there is improving students’ score of this subject of Enterpreneurship by using teamwork of written proposal and writing compile as their individual task.